Kinetics of chlorination of vanadium slag by microwave heating - Bo TAN; Li-jun WANG; Bai-jun YAN; Kuo-chih CHOU (工程科学学报, 2020)
Microwave heating was used in this study to chlorinate the extraction of Fe, Mn, V, and Cr from vanadium slag using AlCl3 molten salt at a temperature range from 500 to 800 °C. Microwave heating chlorination kinetics was studied in a non-isothermal mode. The effects of the AlCl3/vanadium slag mass ratio and molten salt ratio on the extraction rate of chlorination peoducts were investigated. The structure and morphology evolution of microwave heating chlorination products were characterized by X-ray diffraction and scanning electron microscope with energy dispersive spectrometer. The results show that the highest extraction rate of the five elements (Fe, Mn, V, Cr, and Ti) can be achieved as 91.66%, 92.96%, 82.67%, 75.82% and 63.14%, when the mass ratios of AlCl3/vanadium slag and NaCl–KCl/AlCl3 are 1.5 and 1.66, respectively. These extraction rates in the microwave heating mode for 30 min are reached and exceeded by 6 h in the conventional heating method. Microwave heating will minimize the chlorination time and reduce the volatilization of AlCl3. Based on the thermodynamics and kinetic analysis, the different phases of vanadium slag can be chlorinated using AlCl3 in the range from 400 to 800 °C, and the olivine phase is superior to the spinel phase in chlorination. In addition, the chlorination rates of V and Cr are slower than those of Fe and Mn, and increasing the reaction time is advantageous for the chlorination of V and Cr. The chlorination of Fe and Mn is controlled by diffusion, and the non-isothermal diffusion activation energies of Fe and Mn are 17.02 and 17.10 kJ·mol−1, respectively. In contrast, the chlorination of V and Cr is limited in the interfacial chemical reaction step, for whom the activation energies give 40.00 and 50.92 kJ·mol−1, respectively. The combination effect of the microwave and molten salt on the chlorinating vanadium slag can be attributed to the enhancement of the diffusion and local chemical reaction.